Menguak Nilai-Nilai Kearifan Lokal Dan Interelasinya Dengan Islam Membentuk Moderasi Beragama - Armyn Hasibuan (Hikmah, 2025)
This study aims to reveal the ethical and moral values embedded in local wisdom that shape the practice of religious moderation within the community of Batu Godang Village, Angkola Sangkunur Subdistrict, South Tapanuli. This village has been designated as a fostered village and is currently preparing to become a pilot village for the PTP2WKSS (Integrated Program for Enhancing Women’s Roles toward Healthy and Prosperous Families). The research employs a descriptive qualitative approach, with data collected through participatory observation, in-depth interviews, and field documentation. Data analysis was conducted interactively following the Miles and Huberman model, encompassing data reduction, data display, and conclusion drawing. The findings indicate that the Batu Godang community internalizes local wisdom values integrated with Islamic teachings—such as honesty (ṣidq), responsibility (amānah), justice (‘adl), and tolerance (tasāmuḥ)—in interfaith social life, particularly in fostering religious moderation. These values function as the foundation of religious moderation, aligning with the Islamic concept of wasathiyyah as well as the four indicators of religious moderation promoted by the Indonesian Ministry of Religious Affairs: national commitment, tolerance, non-violence, and acceptance of local culture. The integration of Islamic ethical perspectives from Al-Ghazali and Ibn Miskawaih with religious moderation theory demonstrates that spiritual morality, when combined with local wisdom, contributes to the formation of a harmonious, plural, and civilized society